Netizens’ Comments in Responding Polling of Presidential-VP Candidate 2019 on YouTube: Rocky Gerung's Channel - Nico Harared; Irfan Hadi (TEKNOSASTIK, 2020)
The aim of this research is to describe the expressive speech acts of the YouTube user (netizen) and the politeness strategy used by the netizens in line to respond polling of Presidential-VP candidate in Indonesia. This descriptive qualitative research used library research in collecting the data. Some theories related to expressive speech acts and politeness strategy were used to analyze the data. The analysis was represented by using informal method. The result of analysis showed that the expressive speech act is the most frequently used by the YouTube users. The results indicated that the netizens used expressive speech acts to express anger, satirizing, sympathizing, blaming, thanking and fulminating. The research also revealed the importance of expressive speech act in keeping politeness in witten language. It was concluded that the netizens were creative in expressing their ideas through written language. Expressive speech acts and politeness strategy reflected the way the language users show their emotion by using words.